POWERFUL SOCIAL STUDIES LEARNING INTEGRATED WITH DAYAK DEAH LOCAL WISDOM AT JUNIOR HIGH SCHOOLS IN TABALONG - Nadilla, Dewicca Fatma; Syaharuddin, Syaharuddin; Subiyakto, Bambang; Arisanty, Deasy; Jannah, Fathul; Mardiani, Fitri (International Conference On Social Science Education, 2024)
Local wisdom-based approach to create relevant, contextual, and in-depth learning is very important in social studies learning. This study aims to analyze the integration of Dayak Deah local wisdom in learning Social Studies with a powerful learning approach in Tabalong State Junior High School. The research method is qualitative with a case study design, with data collection through interviews, observations, and document analysis to obtain data from teachers, students, and principals. The results showed that the integration of Dayak Deah local wisdom, such as the tradition of farming in shifts and the preservation of customary forests, was able to improve students' understanding of the concept of sustainability, the relationship between humans and nature, and socio-cultural values. Activities such as simulation of customary traditions and direct observation of the community provide a more contextual and meaningful learning experience. However, challenges such as teachers' limited understanding of local wisdom and the lack of local culture-based teaching materials affect the effectiveness of implementation. The conclusion of this study confirms that the powerful learning approach is relevant to improve the quality of local wisdom-based learning. With teacher training, teaching material development and digital documentation of local values, this model can be more widely adopted as a sustainable education strategy in Indonesia.